2007
DOI: 10.1007/s10350-007-0294-6
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Hemorrhoidopexy and Milligan Morgan Hemorrhoidectomy in the Cure of Fourth-Degree Hemorrhoids: Long-Term Evaluation and Clinical Results

Abstract: Long follow-up seems to indicate more favorable results in Milligan-Morgan procedure in terms of resumption of symptoms and risk of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 26 publications
3
34
0
5
Order By: Relevance
“…In some studies comparing these two methods, no statistically significant difference was determined. 2,26,32 In a study done by Jayaraman et al by considering 12 studies, they reported high recurrence rates in the long term after stapled hemorrhoidopexy particularly in 4 th degree hemorrhoid cases. 33 In our study, low recurrence rate was attributed to small number of 4 th degree hemorrhoid cases operated.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies comparing these two methods, no statistically significant difference was determined. 2,26,32 In a study done by Jayaraman et al by considering 12 studies, they reported high recurrence rates in the long term after stapled hemorrhoidopexy particularly in 4 th degree hemorrhoid cases. 33 In our study, low recurrence rate was attributed to small number of 4 th degree hemorrhoid cases operated.…”
Section: Discussionmentioning
confidence: 99%
“…According to some authors, recurrent rectal prolapse was significantly more frequent in patients with fourth-degree hemorrhoids, so that they may not represent an appropriate indication for stapled hemorrhoidopexy [49,50,76]. Actually, in patients with only third-degree hemorrhoids, recurrence is similar in both stapled hemorrhoidopexy and conventional hemorrhoidectomy [77].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, however, few authors have raised some serious questions about the long term results of this technique and its generalized applications over almost all grades of the prolapsing hemorrhoids. [10][11][12] This trial has clearly addressed these issues in a systematic way.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although the short term benefits have been clearly documented in multiple clinical trials comparing these two techniques; questions have been raised regarding long term outcome of this newer approach. [10][11][12] Recent studies including a recent meta-analysis suggest that long term recurrence rates are higher with stapled hemorrhoidectomy as opposed to the conventional hemorrhoidectomy. [10][11][12] This study is a prospective randomized trial comparing the patients undergoing stapled hemorrhoidectomy vs. conventional hemorrhoidectomy to answer particular questions regarding its efficacy and failure rates on a longterm follow up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation